Controlling thermal emission with refractory epsilon-near-zero metamaterials via topological transitions - P. N. Dyachenko (Nature Portfolio, 2016)
The ability to control thermal radiation at high temperatures is of interest for thermal photovoltaics. Here, Dyachenko et al. engineer the epsilon-near-zero frequency of a metamaterial and connected optical topological transition to selectively enhance and suppress the thermal emission in the near-infrared spectrum.